A dinâmica do crescimento e distribuição : uma revisão sobre os modelos heterodoxos de crescimento - Carvalho, Bruno Henrique Picon de (2016)
This study aimed to carry out a theoretical review of the origin and evolution of heterodox growth models, focusing on the relationship between the distribution and growth, comparing the different frameworks, their hypotheses and onclusions, always showing the interrelationships and theoretical clashes between these schools. Modern growth theory originated from the independent contributions of Harrod and Domar, who wished to build a Keynesian model for the long term. The main conclusion of these authors is that there is only one equilibrium growth rate and, once this system is distanced, by a long depression would (if distance itself down) or inflation (if grow above). This result was criticized by the school of Cambridge, who developed a solution through flexible savings function. Since the capitalists save more workers, any redistribution to profits raise the savings rate, and decrease with the increase of wages. Through this mechanism, stability can be obtained, and there was an inverse relationship between distribution and growth. At the same time, Kalecki developed his theory of effective demand, the standing in an environment characterized by the presence of oligopolies and price formed via mark-up. Moreover, the author concludes that there is a direct relationship between growth and accumulation, because the salary increase does not lead to falling profits. In turn, Josef Steindl kaleckiano used the framework to build an endogenous explanation for the tendency of mature capitalism to stagnation in contrast to the dominant explanation related to the reduction of technological innovations. According to the author, the presence of oligopoly the only way the firm reacting a negative impact on the capital accumulation is by reducing the use of the plant. However, the resulting idleness makes the resolute entrepreneurs to pursue new investment, stagnating the economy. As theorists of Keynesian growth saw the need to abandon the hypothesis of full employment in this school of Cambridge, the same sought inspiration from Kalecki and Steindl, giving rise to neo-Kaleckian models. In these, as in Steindl, there is a direct relationship between distribution and growth, so that the concentration of income and increased mark-up would induce a stagnation process. The neo-Kaleckian received two different types of criticism, the first essentially linked to the neo-Ricardian approach, consisting of the refusal of this instability in the long neo-kaleckiano term, which would not be compatible with a long-term equilibrium position and the second, related to the existence of a positive relationship between distribution and growth, analysis of which highlights the Bhaduri and Marglin (1990), which was fully digested. According to these authors, the increase in real wages has two distinct effects, increased consumption and reduced investment. If the first effect is greater than the second, there will be an incentive on demand, and thus will be in the wage-led regime. In turn, if the reduction of the investment is more pronounced, wage improvement will reduce the total demand, characterizing the profit-led regime. Therefore, the relationship between distribution and growth depend on how business decision reacts to changes in the rate of profit and therefore cannot be defined a priori. Thus, it was concluded that the evolution of heterodox growth models did not occur in a linear and harmonic way, with a paradigm replacing the other, but through a complex process as many arguments have been developed in parallel or returning later on new guise.